Respuesta :

[tex]ax + by = a - b \: \: \: ...(i)\\ \\ bx - ay = a+ b \: \: \: ...(ii) \\ \\ [/tex]

Multiply equation (i) with a and equation (ii) with b ,

[tex] {a}^{2} x + aby = {a}^{2} - ab \: \: \: ...(iii)\\ \\ {b}^{2} x - aby = ab + {b}^{2} \: \: \: ...(iv)[/tex]

Adding (iii) and (iv) , we get ,

[tex]( {a}^{2} + {b}^{2} )x = {a}^{2} + {b}^{2} \\ \\ x = 1[/tex]

Now , from (i) ,

[tex]ax+by=a−b \\ \\ a+by=a−b\\ \\ by=−b \\ \\ y=−1[/tex]

Answer: x = 1, y = -1

Step-by-Step Explanation:

As the answer involves many steps, I’ve taken a pic of my working. Please check the attached photo.
Ver imagen Sidharth999
ACCESS MORE